2009
DOI: 10.1097/pec.0b013e3181a341ac
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Admissions in a Pediatric Resuscitation Room

Abstract: In addition to national guidelines for PRR management, the teaching and knowledge of the different diagnosis admitted in the PRR and their resuscitation technical procedures warranty a serener approach of those stressful situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
1
14
1
2
Order By: Relevance
“…The rhythms included ventricular fi brillation (VF), pulseless ventricular tachycardia, pulseless electrical activity (PEA), and asystole. In this study, VF includes patients with pulseless ventricular tachycardia.The etiologies of ICU admissions were divided into seventeen major categories: (1) conditions originating in the peri-natal period; (2) diseases of the respiratory system; (3) injury and poisoning; (4) infectious and parasitic diseases; (5) diseases of the nervous system and sense organs; (6) symptoms, signs and ill-defi ned conditions; (7) congenital abnormalities; (8) diseases of the digestive system; (9) diseases of the circulatory system; (10) diseases of the blood and blood-forming organs; (11) endocrine, nutritional, metabolic and immunity disorders; (12) diseases of the genitourinary system; (13) diseases of the skin and subcutaneous tissue; (14) neoplasms; (15) mental disorders; (16) diseases of the musculoskeletal system and connective tissue; and (17) complications of pregnancy, childbirth, and the puerperium. Correlations between related factors, including gender, age, hospital course, and diff erent years and etiologies, were also analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…The rhythms included ventricular fi brillation (VF), pulseless ventricular tachycardia, pulseless electrical activity (PEA), and asystole. In this study, VF includes patients with pulseless ventricular tachycardia.The etiologies of ICU admissions were divided into seventeen major categories: (1) conditions originating in the peri-natal period; (2) diseases of the respiratory system; (3) injury and poisoning; (4) infectious and parasitic diseases; (5) diseases of the nervous system and sense organs; (6) symptoms, signs and ill-defi ned conditions; (7) congenital abnormalities; (8) diseases of the digestive system; (9) diseases of the circulatory system; (10) diseases of the blood and blood-forming organs; (11) endocrine, nutritional, metabolic and immunity disorders; (12) diseases of the genitourinary system; (13) diseases of the skin and subcutaneous tissue; (14) neoplasms; (15) mental disorders; (16) diseases of the musculoskeletal system and connective tissue; and (17) complications of pregnancy, childbirth, and the puerperium. Correlations between related factors, including gender, age, hospital course, and diff erent years and etiologies, were also analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies, however, have showed most of the children are being younger than 1 year. 1,13,14 There is a possible explanation for increased numbers of preschool children in our study. While our hospital has one of the most advanced pediatric intensive care units in available in Turkey, it has a comparatively smaller neonatal intensive care unit.…”
Section: Discussionmentioning
confidence: 82%
“…In our study group, 41% of the surgical patients were admitted to the ICU, in comparison with other studies showing admittance to the ICU of less than 20%. 6,12 Although patient safety is the most important aspect and therefore patient should be liberally treated in the resuscitation bay, this is definitely an aspect that needs constant reevaluation and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the main causes seemed to be neurological, respiratory, cardiocirculatory problems, and trauma. 6,7 As previous studies have shown, video recording is more effective than medical record review in detecting management errors in pediatric trauma resuscitation. 8,9 Therefore, the aim of our study was to analyze the adherence to advanced trauma life support (ATLS) and PALS guidelines and identify management errors in the pediatric resuscitation bay by using video recordings.…”
mentioning
confidence: 99%